Fully coupled modeling of seabed subsidence and reservoir compaction of North Sea oil fields - Lewis, Roland W (Springer-Verlag, 2003)
This paper focuses on the aspects of fully coupled continuum modeling of multiphase poroelasticity applied to the three-dimensional numerical simulations of the Ekofisk oil reservoir in the North Sea (56°29′–34′N, 03°10′–14′E). A systematic presentation is chosen to present the methodology behind fully coupled, continuum modeling. First, a historical review of the subsidence phenomena above an oil and gas reservoir is given. This will serve as a background against which the relevance of the present approach to compaction and subsidence modeling will be demonstrated. Following this, the governing equations for a multiphase poroelasticity model are briefly presented. Particular attention is paid to the analysis of the pore-compressibility term usually used in an uncoupled approach for characterising the host-rock deformation. A comparative numerical analysis is carried out to contrast and highlight the difference between coupled and uncoupled reservoir simulators. Finally, a finite-element numerical model of the Ekofisk field is presented and a significant result is a contour map of seabed subsidence which is in general agreement with the shape of the subsidence contours based on past bathymetric surveys. Analysis of the simulation reveals that, due to the downward movement of the overburden, oil migration occurs from the crest of the anticline in which the field is situated, towards the flank. The porepressure depletion in the reservoir is significantly delayed due to the replenishment of the reservoir energy via the formational compaction. Horizontal movement in the reservoir, which is neglected in traditional modeling, can be significant and comparable in magnitude to the vertical subsidence.